2021
DOI: 10.1101/2021.02.24.432431
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mammalian adipogenesis regulators (Aregs) exhibit robust non- and anti-adipogenic properties that arise with age and involve retinoic acid signalling

Abstract: Adipose stem and precursor cells (ASPCs) give rise to adipocytes and determine the composition and plasticity of adipose tissue. Recently, several studies have demonstrated that ASPCs partition into at least three distinct cell subpopulations: Dpp4+ stem-like cells, Aoc3+ pre-adipocyte-like cells, and the enigmatic CD142+ cells. A great challenge now is to functionally characterize these distinct ASPC populations. Here, we focus on CD142+ ASPCs since discrepant properties have been assigned to this subpopulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 53 publications
(127 reference statements)
0
1
0
Order By: Relevance
“…Recent studies employing single-cell RNA-sequencing technology have revealed subpopulations of Pdgfrα+ cells, including Dpp4+/Pi16+ ‘progenitors’, Icam1+/Col15a1+ ‘preadipocytes’, and Cd142+ ‘adipose regulatory cells’, as well as additional cell types [ [32] , 33 , [34] , [35] , [36] , [37] , [38] ]. Dpp4+ cells possess enhanced proliferative capacity and multilineage differentiation potential [ 32 , 39 ]. By contrast, Icam1+ cells are highly committed to the adipose lineage and rapidly undergo adipocyte differentiation with minimal stimulus.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies employing single-cell RNA-sequencing technology have revealed subpopulations of Pdgfrα+ cells, including Dpp4+/Pi16+ ‘progenitors’, Icam1+/Col15a1+ ‘preadipocytes’, and Cd142+ ‘adipose regulatory cells’, as well as additional cell types [ [32] , 33 , [34] , [35] , [36] , [37] , [38] ]. Dpp4+ cells possess enhanced proliferative capacity and multilineage differentiation potential [ 32 , 39 ]. By contrast, Icam1+ cells are highly committed to the adipose lineage and rapidly undergo adipocyte differentiation with minimal stimulus.…”
Section: Introductionmentioning
confidence: 99%